Instructor`s notes for the case study `Introduction of a new bean variety in La Merced` - Herpen, D. van (International Center for Tropical Agriculture, 1991)
Instructions (general teaching notes, case study instruction), on how to apply the exercise on the case study introduction of a new bean var. in La Merced, Colombia, are given. An example of case study analysis is also provided. (CIAT)